Отсроченный шанс, или Подарок из прошлой жизни: роман / Татьяна Алюшина - Алюшина Татьяна Александровна (Эксмо, 2022)
Экземпляры: ф.17 (20240520) / Инвентарный номер: 64723 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44